Pathways To Development : What We Know and Don't Know - Nallari, Raj (2012)
Sixty years of development experience tells us that the pathways to development are varied, guided by different visions, different strategies, and different definitions of progress. If sustained growth is the measure, then progress has also been mixed. Between 1990 and 2008, the developing economies have grown nearly twice as fast on average as the developed countries. But over the past six decades, only a dozen countries have sustained their growth for twenty years or more because of frequent shocks, redistributive conflicts, and difficulty in sustaining reform efforts over time.